Prevalence and Correlates of Mild Cognitive Impairment in Older Outpatients: A Cross-Sectional Study. - Nguyen, Khai Quang; Than, The Ha Ngoc; To, Kien Gia (Inquiry (00469580), 2026)
To estimate the prevalence of screen-detected mild cognitive impairment (MCI) and identify associated sociodemographic, lifestyle, and functional factors among older adults attending outpatient care in a low- and middle-income country. A cross-sectional study was conducted between May 2024 and February 2025 among adults aged ≥60 years attending an outpatient department in southern Vietnam. Data were collected through interviews and standardized assessments, including the Mini-Mental State Examination and the Lawton Instrumental Activities of Daily Living scale. Associations were examined using logistic regression. Of 631 participants, 30.1% screened positive for MCI. Older age, unmarried status, unstable income, lower education, reduced recreational activity, and lower IADL scores were associated with higher odds of MCI, with age and recreational inactivity showing the strongest effects. The high prevalence of MCI among older outpatients highlights the need to integrate cognitive and social-functional screening into outpatient care in resource-limited settings. Enhancing recreational and social engagement may mitigate early cognitive decline.